Phencyclidine dose optimisation for induction of spatial learning and memory deficits related to schizophrenia in C57BL/6 mice - Zain, Mohd Aizat Mohd; Rouhollahi, Elham; Pandy, Vijayapandi; Mani, Vasudevan; Majeed, Abu Bakar Abdul; Wong, Won Fen; Mohamed, Zahurin (Japanese Association for Laboratory Animal Science, 2018)
Phencyclidine (PCP) has been used to model cognitive deficits related to schizophrenia in rats and mice. However, the model in mice is not consistent in terms of the PCP effective dose reported. Furthermore, most of the previous studies in mice excluded the presence of drug washout period in the regime. Thus, we aimed to optimize the dose of PCP in producing robust cognitive deficits by implementing it in a PCP regime which incorporates a drug washout period. The regimen used was 7 days’ daily injection of PCP or saline for treatment and vehicle groups, respectively; followed by 24 h drug washout period. After the washout period, the test mice were tested in water maze (5 days of acquisition + 1 day of probe trial) for assessment of spatial learning and memory. Initially, we investigated the effect of PCP at 2mg/kg, however, no apparent impairment in spatial learning and memory was observed. Subsequently, we examined the effect of higher doses of PCP at 5, 10 and 20 mg/kg. We found that the PCP at 10 mg/kg produced a significant increase in “latency to reach the platform” during the acquisition days and a significant increase in “latency of first entry to previous platform” during the probe day. There was no significant change observed in “swim speed” during the test days. Thus, we concluded that PCP at 10 mg/kg produced robust deficits in spatial learning and memory without being confounded by motor disturbances.